(untitled) (Journal of Governance and Development (JGD), 2022)
The major thrusts of regional development are to achieve balances in social and economic development across regions and states and to raise the standard of living and quality of life of the people. Consequently, developments of border areas of Malaysia and Thailand, particularly the border towns of Northern Corridor Economic Region (NCER), i.e. Wang Kelian (Perlis), Padang Besar (Perlis), Bukit Kayu Hitam (Kedah), Durian Burong (Kedah), and Pengkalan Hulu (Perak) will benefit the people living in the border areas and for the mutual benefits of the two countries. It further promotes greater cooperation in trade and investment in the border areas. Therefore, there is a need to conduct a feasibility study and to take strategic approach in developing special border economic zone to ensure that whatever development would not be in conflict with the states’ interest or policies in relation to the development of such border areas.